Assessments of risk of bias in systematic reviews of observational nutritional epidemiologic studies are often not appropriate or comprehensive: a methodological study. Issue 2 (7th December 2021) - Zeraatkar, Dena; Kohut, Alana; Bhasin, Arrti; Morassut, Rita E; Churchill, Isabella; Gupta, Arnav; Lawson, Daeria; Miroshnychenko, Anna; Sirotich, Emily; Aryal, Komal; Azab, Maria; Beyene, Joseph; et al.
Abstract : Background: An essential component of systematic reviews is the assessment of risk of bias. To date, there has been no investigation of how reviews of non-randomised studies of nutritional exposures (called 'nutritional epidemiologic studies') assess risk of bias. Objective: To describe methods for the assessment of risk of bias in reviews of nutritional epidemiologic studies. Methods: We searched MEDLINE, EMBASE and the Cochrane Database of Systematic Reviews (Jan 2018–Aug 2019) and sampled 150 systematic reviews of nutritional epidemiologic studies. Results: Most reviews (n=131/150; 87.3%) attempted to assess risk of bias. Commonly used tools neglected to address all important sources of bias, such as selective reporting (n=25/28; 89.3%), and frequently included constructs unrelated to risk of bias, such as reporting (n=14/28; 50.0%). Most reviews (n=66/101; 65.3%) did not incorporate risk of bias in the synthesis. While more than half of reviews considered biases due to confounding and misclassification of the exposure in their interpretation of findings, other biases, such as selective reporting, were rarely considered (n=1/150; 0.7%). Conclusion: Reviews of nutritional epidemiologic studies have important limitations in their assessment of risk of bias.